Jorge praying - Cayetano Contreras, Jr.:::photographer::: (2025)
Photo caption, written by Cayetano Contreras, Jr.: 'This is my little brother Jorge praying in [at?] our kitchen table. He is asking God to forgive him for all the tricks he's played on our mom.'